REFLECTION AND ACTION: PRINCIPALS WORKING TOWARDS SOCIAL JUSTICE IN THEIR SCHOOLS - (:unkn) unknown (My University, 2024)
As the disparity gap in U.S. schools continues to persist, school districts and their leaders look for ways to address this issue. In recent years, there have been multitude of attempts to remedy this concern through various trainings programs. Year after year, Wisconsin ranks number one for the largest disparity gap between Black and White students. Using a qualitative multiple-case study approach, this study explored the instructional and engagement practices of six principals in the Fox River Valley Region. This study asked -- how do principals transform their practices to create a more socially just learning environment? More specifically: how do principals interpret the role of equity in implementing their school’s instructional practices and how are equity practices reflected in principals’ engagement with students and parents of marginalized groups. Semi-structured interviews with individual principals and a focus group interview were conducted, as well as a review of equity related documents. The collected data was analyzed using a coding process to look for emergent themes. Four themes surfaced from the data which include: (1) Transforming and Empowering through Leadership, (2) Inclusivity: All Means All, (3) It’s All About Relationships, (4) The Value of Voice in Equity. This study found that these principals’ social justice practices were at various levels ranging from emerging to more advanced and that other practices led to marginalization.
Keywords: Educational administration; Equity; Principals; Social Justice